Coping strategies and resources of volunteer telephone counsellors at a South African organisation: An exploratory study - Cerf, Tayla (Department of Psychology, 2025)
Telephone counsellors are significant assets in communities where numerous treatment barriers restrict individuals from accessing professional mental health care. However, working on a crisis line can be detrimental to volunteers' well-being, creating risk for secondary trauma, burnout and vicarious trauma. While these risks are well-established, there is considerably less research on the coping strategies and resources that can support telephone counsellors in their work and protect them from negative impacts. The current study explored telephone counsellors' work-related challenges and the coping strategies and resources they use to manage the impact of their work on their professional and personal lives. A qualitative study was conducted with twelve participants at a South African telephone counselling organisation. Participants were interviewed using a semi-structured interview schedule and reflexive thematic analysis was used to interpret and make meaning of the participants' lived experiences. The following eight themes emerged: challenging calls, negative impacts on the self, frustration with telephone counselling conditions, mindful practices to cope with telephone counselling challenges, active engagement with counselling experiences, actively disengaging from counselling experiences, coping through connection, and hopes for coping in the future. The findings indicate that although participants felt professionally and personally challenged by the nature of telephone counselling work, they were cognizant of how best to support themselves and seemed to find their role manageable and meaningful even when faced with adverse counselling experiences. The coping strategies and resources identified by the participants could inform counsellor support initiatives at crisis lines in South Africa and elsewhere.